2021
DOI: 10.1002/ehf2.13290
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N‐oxide and outcomes in patients hospitalized with acute heart failure and preserved ejection fraction

Abstract: Aims Trimethylamine N-oxide (TMAO) is a metabolite derived from the gut microbiota. Elevated TMAO levels are associated with a poor prognosis in patients with heart failure with reduced ejection fraction. However, the prognostic effect of elevated TMAO levels on heart failure with preserved ejection fraction (HFpEF) remains unclear. Methods and results We consecutively enrolled 146 patients who were hospitalized and discharged from Tottori University Hospital with the primary diagnosis of HFpEF (ejection fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Of these, 79 reports lacked relevant data, and two articles were excluded because of data duplication. Ultimately, four cohort studies (21,(25)(26)(27), one nested casecontrol study (22), and one cross-sectional study (28) were included in our meta-analysis, with a total of 8,837 patients, including 1,668 patients with AF. The flow chart for the study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 79 reports lacked relevant data, and two articles were excluded because of data duplication. Ultimately, four cohort studies (21,(25)(26)(27), one nested casecontrol study (22), and one cross-sectional study (28) were included in our meta-analysis, with a total of 8,837 patients, including 1,668 patients with AF. The flow chart for the study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Reports in the current meta-analysis mainly investigated the role of TMAO in the bloodstream of patients who had different diseases, including kidney disease (28), acute and chronic heart failure (CHF) (25)(26)(27), and suspected stable angina pectoris (21). Two studies did not directly give the average circulating TMAO concentration of patients (21,22).…”
Section: Study Characteristics and Qualitative Evaluationmentioning
confidence: 99%
See 3 more Smart Citations